The Impact of Merapi Mountain Eruption on the Community Economy - Yudistira, Danu; Fadilah, Ririn Nur; Setiawan, Avi Budi (Universitas Negeri Semarang, 2020)
The impact of the Mount Merapi Eruption has positive and negative impacts on the economy of the community, especially in the agricultural sector. Therefore, the purpose of this study is to analyze the impact of the Mount Merapi Eruption on the economy of the people of Sleman Regency, Magelang Regency, and Klaten Regency in terms of the potential sector in the Regency, that is agriculture. Thus it can be used as one of the considerations to boost and develop the agricultural sector. This study uses secondary data from BPS (Central Statistics Agency) Magelang regency in the form of rice production within a period of 3 years, 2010-2012. Based on the results of the analysis, it can be seen that regional income has decreased after the disaster in 2010. The agricultural sector which is the primary sector and the leading / base sector has decreased in contribution so that it shifts its role to the non-base sector. However, variations occurred in some regions in the district to meet their daily needs, eventually turning into a non-base profession. The results of this study see that the impact of the eruption of Mount Merapi on economic productivity in Sleman Regency, Magelang Regency and Klaten Regency. Dampak Erupsi Gunung Merapi memiliki dampak positif dan negatif terhadap ekonomi masyarakat, terutama di sektor pertanian. Oleh karena itu, tujuan dari penelitian ini adalah untuk menganalisis dampak Erupsi Gunung Merapi terhadap perekonomian masyarakat Kabupaten Sleman, Kabupaten Magelang, dan Kabupaten Klaten dalam hal sektor potensial di Kabupaten tersebut, yaitu pertanian. Dengan demikian dapat digunakan sebagai salah satu pertimbangan untuk mendorong dan mengembangkan sektor pertanian. Penelitian ini menggunakan data sekunder dari BPS (Badan Pusat Statistik) Kabupaten Magelang dalam bentuk produksi beras dalam kurun waktu 3 tahun, 2010-2012. Berdasarkan hasil analisis, dapat dilihat bahwa pendapatan daerah mengalami penurunan setelah bencana tahun 2010. Sektor pertanian yang merupakan sektor primer dan sektor unggulan / sektor basis mengalami penurunan kontribusi sehingga menggeser perannya ke sektor berbasis. Namun, variasi terjadi di beberapa daerah di kabupaten untuk memenuhi kebutuhan sehari-hari mereka, yang pada akhirnya berubah menjadi profesi yang tidak berbasis. Hasil penelitian ini melihat bahwa dampak erupsi Gunung Merapi terhadap produktivitas ekonomi di Kabupaten Sleman, Kabupaten Magelang dan Kabupaten Klaten.